A Comprehensive Study of Routing Layer Intrusions in Zig Bee based Wireless Sensor Networks - Monika Sachdeva, Navjot Sidhu (International Journal of Advanced Science and Technology, 2020)
The security of Wireless Sensor Network is a critical research topic these days. The major issue in such networks, is the vulnerability of routing protocols to network attacks. Most of the researchers have studied several possible attacks in these networks either considering different proposed routing algorithms or in general. However, actual sensor nodes work only on standardized protocol stack. Therefore, ZigBee Wireless Sensor Network is considered to present the impact and consequences of routing attacks in this paper. Additionally, the theoretical analysis of possible attacks in Ad-hoc on Demand Distance Vector routing protocol is presented in terms of attacker’s actions and goals behind such intrusions in sensor networks. This study is advantageous for the research community to implement these attacks in test-bed or simulated environments. So that the impact of attacks can be captured correctly and the timely detection of these intrusions can be proposed for resource constrained wireless sensor networks.